Tindak Tutur Komisif Dalam Debat Capres Pilpres 2024 Serta Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMA - Zamani, Faiz Alex; Islam, Muhammad Hifdzil; Hamdiah, Magfirotul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Commissive speech is speech that is realized through promises and is often realized in various activities. Debate is one of the activities that realizes the form of commissive speech in it. This research aims to analyze the form of commissive speech acts in the 2024 presidential election debate and its implications for Indonesian language learning in high school. This research is qualitative research with descriptive research type. . The data in this research is in the form of excerpts from the speeches of the presidential debate candidates which are commissive in nature and their implications for Indonesian language learning in high school. The data source in this research is a video about the presidential candidate debate episode 1 which was accessed via the Kompas TV Youtube Channel. The data collection technique in this research is used through several stages, namely listening, taking notes, data classification and data description. Then the data is analyzed through a data condensation process and continues with the data presentation stage.Keyword: Commissive Speech, Presidential debate, Indonesian Language Learning.